GR_GERICHTE ZF 2008 64 vom 10. November 2008 , OR Auftrag/Gesch\x27führung o. Auftrag/Bürgschaft etc. (OR 394-529) - GR Gerichte (2008)
Ehevorbereitungsverfahren/Vorbereitung einer Vaterschaftsanerkennung | Leitentscheid, publiziert als PKG 2009 3\x3Cbr\x3E | ZGB Eherecht